2021
DOI: 10.2174/1566523221666211202095258
|View full text |Cite
|
Sign up to set email alerts
|

CircRNAs in Lung Adenocarcinoma: Diagnosis and Therapy

Abstract: : Lung adenocarcinoma (LUAD) is the common histological subtype of non-small-cell lung carcinoma (NSCLC). Circular RNAs (circRNAs) represent a new class of non-coding RNAs (ncRNAs) involved in the development of cancer. Accumulating evidence indicated that a large number of circular RNAs were found to be involved in many biological processes, including tumor initiation, proliferation and progression. These circRNAs present great potentials as new biomarkers and vital targets for disease diagnosis and prognosis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 73 publications
2
9
0
Order By: Relevance
“…In recent decades, much attention has been paid on the molecular mechanisms underlying the pathogenesis of LUAD, and the epigenetic alternations and gene mutations take up an important reason contributing to the regulation of LUAD development. [20][21][22] In the present study, we demonstrated aberrant upregulation of NPAS2 and ARRB1 in LUAD cell lines. ARRB1 was found to be a critical transcription factor of NPAS2 with binding sites within the promoter region of NPAS2, thereby causing its transcriptional activation.…”
Section: Discussionsupporting
confidence: 64%
See 1 more Smart Citation
“…In recent decades, much attention has been paid on the molecular mechanisms underlying the pathogenesis of LUAD, and the epigenetic alternations and gene mutations take up an important reason contributing to the regulation of LUAD development. [20][21][22] In the present study, we demonstrated aberrant upregulation of NPAS2 and ARRB1 in LUAD cell lines. ARRB1 was found to be a critical transcription factor of NPAS2 with binding sites within the promoter region of NPAS2, thereby causing its transcriptional activation.…”
Section: Discussionsupporting
confidence: 64%
“…LUAD has become a great threat to public health, accompanied by increased morbidity and mortality in women worldwide. In recent decades, much attention has been paid on the molecular mechanisms underlying the pathogenesis of LUAD, and the epigenetic alternations and gene mutations take up an important reason contributing to the regulation of LUAD development 20–22 . In the present study, we demonstrated aberrant upregulation of NPAS2 and ARRB1 in LUAD cell lines.…”
Section: Discussionsupporting
confidence: 61%
“…This is likely due to the fact that lung adenocarcinoma can infiltrate and grow into the bronchial cavity, adjacent lung tissue, and other organs, as well as spreading to other sites through lymphatic and hematogenous routes. Therefore, most patients are difficult to be diagnosed at an early stage and are often reached when detected, leading to a poor prognosis ( 6 ).…”
Section: Introductionmentioning
confidence: 99%
“…Lung adenocarcinoma (LUAD) is a common type of non‐small cell lung cancer (NSCLC) that originates in the bronchial mucosal epithelium and is more common in nonsmoking women 1,2 . Despite these efforts, there is still much room for improvement in the treatment options for LUAD patients 3,4 .…”
Section: Introductionmentioning
confidence: 99%